Ventilatory and anthropometric variables in healthy female students from the University of Ljubljana - Zerbo Šporin, Dorjana (Acta biologica slovenica, 2002)
Forced expiratory vital capacity (FEVC) and forced expiratory volume in the first second (FEV1) were measured in healthy, non-smoking female students fromthe University of Ljubljana. The sample included 86 students, none active in sports, ranging in age from 18-23 years. The results were analysed in termsof anthropometric variables, and regressiori equations were derived. Comparisons were made with Europaean Respiratory Society (ERS) prediction equations derived from non-Slovenian populations, commonly used in our medicalpractice. The ERS and our equations predict significantly different values for FEVC and insignificantly for FEV1. According to comparisons of r2 and SD of residuals, we presumed that newly derived equations can be better predictors of ventilatory parameters for Slovene female students population.
Keywords: Adult; Anthropometry; Antropometrija; Body Height; Body Weight; fiziologija; Forced Expiratory Volume; Forsirani, ekspiratorni volumen; Odrasli; Spirometrija; Spirometry; Students; Študenti; študentke; Telesna teža; Telesna višina; Vital Capacity; Vitalna kapaciteta